FRAUD PREVENTION: AN REVIEW THROUGH GOOD CORPORATE GOVERNANCE AND INDIVIDUAL MORALITY - HM. Ridlwan Hambali; Sunday Ade Sitorus; Teguh Setiawan Wibowo; Asri Ady Bakri; Bambang Sucipto; SUNDAY ADE SITORUS (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2023)
This research is motivated by an increase in fraud cases in companies. This study aims to determine and analyze the influence of good corporate governance and individual morality on fraud prevention. The research method used in this research is descriptive method with a quantitative approach. The sample in this study were 100 employees using random sampling technique. Data collection using questionnaires distributed to company employees. The instruments used have been tested for validity and reliability. The collected data were analyzed using the classical assumption test and multiple linear regression with SPSS tools. The results of this study indicate that 1) Good corporate governance has a positive and significant effect on fraud prevention, 2) Individual morality has a positive and significant effect on fraud prevention, and 3) Good corporate governance and individual morality have a positive and significant effect on fraud prevention. The findings of this study suggest that if companies want to improve fraud prevention, companies must also improve good corporate governance and individual morality.